Systematic review: a systems innovation perspective on barriers and facilitators for the implementation of healthy food-store interventions - Cédric N. H. Middel; Tjerk Jan Schuitmaker-Warnaar; Joreintje D. Mackenbach; Jacqueline E. W. Broerse (BMC, 2019)
Abstract Background Due to their central position in the modern food system, food stores present a unique opportunity to promote healthy dietary behaviour. However, there is a lack of insight into the factors that impede or enhance the implementation of nutritional interventions in food stores. We applied a systems innovation and implementation science framework to the identification of such barriers and facilitators. Methods We conducted a systematic literature review. A search string was developed to identify qualitative and quantitative articles on environmental nutritional interventions in the food store. Four databases were systematically searched for studies published between 2000 and 2018. Eligible publications described study designs or original studies, focused on stimulating healthier dietary behaviour through environmental changes in retail settings and contained information on the perceptions or experiences of retailers or interventionists regarding the implementation process of the intervention. Context-descriptive data was extracted and a quality assessment was performed. Results We included 41 articles, of which the majority was conducted in the USA and involved single stores or a mix of single and multi-store organisations. We categorized barriers and facilitators into 18 themes, under five domains. In the 'outer setting' domain, most factors related to consumers' preferences and demands, and the challenge of establishing a supply of healthy products. In the 'inner setting' domain, these related to conflicting values regarding health promotion and commercial viability, store lay-out, (insufficient) knowledge and work capacity, and routines regarding waste avoidance and product stocking. In the 'actors' domain, no major themes were found. For the 'intervention 'domain', most related to intervention-context fit, money and resource provision, material quality, and the trade-offs between commercial costs and risks versus commercial and health benefits. For the 'process' domain, most factors related to continuous engagement and strong relationships. Conclusions This review provides a comprehensive overview of barriers and facilitators to be taken into account when implementing nutritional interventions in food stores. Furthermore, we propose a novel perspective on implementation as the alignment of intervention and retail interests, and a corresponding approach to intervention design which may help avoid barriers, and leverage facilitators. Trial registration PROSPERO; CRD42018095317.